The castaways - Lawrence, Iain, 1955- (Delacorte Press, 2007)
Adrift at sea with four convict companions, Tom and the boys come upon a deserted ship, but unforeseeable events lead Tom to discover that for his own survival, he must make unimaginable decisions.